THE DIFFERENTSOURCESOF PROTEIN FORTIFIED IN PRODUCING OF SAGO INSTANT NOODLES - Mhd Fadhli, Mhd Fadhli; Syahrul, Syahrul; Buchari, Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The objective of the research was to observe the effect of different protein source fortified on the quality of sago instant noodle determined bysensory evaluation and proximate analysis. The research used experimental method and composed to completely randomized design (CRD). The treatments conducted were fortifying the different sourcesof protein into the sago instant noodles, including:theChlorellapowder concentration, dried anchovy powder and rebon shrimp powder, varied into 3 levels, namely: MC (added of5% Chlorellapowder),MT (added of10% dried anchovy powder), MU (added of10% rebonshrimp powder). Quality assessments used were the proximate nutritive values (content of water, fat, protein, ash, and carbohidrates) and sensory evaluation. Results showed that the different source of protein fortified in producing of sago instant noodlesindicated the significant effect on theconsistence but not significant on the aroma, texture and taste of the sago instant noodlesproduced. Meanwhile, the treatments were indicated significant different to the content of water, protein, carbohidrate and NPN but not significant to the content of ash and fat. The best treatment is MU (added of10% rebonshrimp powder) indicated by the highest value of sensory evaluation (consistence 6,33%, aroma 6,17%, texture 5,32%, taste 5,29, the content of protein18.11%, fat 8.60%, carbohydrates42.69%, the value of NPN 0,69%. Key-words : sago noodle, Chlorella, dried anchovy, rebon shrimp